Financial indicators signalling correlation changes in sovereign bond markets - Roberto A. De Santis; Michael Stein (European Central Bank (ECB), 2014)
We use a Smooth Transition Conditional Correlation GARCH (STCC-GARCH) model applied to the euro area monetary policy rates and sovereign yields of Italy, Spain and Germany at 5-year maturity to estimate the threshold level of the signals above which the sovereign bond market moves to a crisis regime. We show that the threshold to a crisis regime for Italy and Spain is reached when (i) their 5-year sovereign yield spreads amount to 80-90 basis points; (ii) their 5-year CDS spreads amount to 120-130 basis points or (iii) the 5-year spread between the Kreditanstalt für Wiederaufbau (KfW) bond and the German Bund amounts to 25 basis points. Using impulse responses, we find that the STCC-GARCH with the KfW-Bund spread has leading properties, a feature corroborated by the fact that this indicator suggested a shift to a crisis regime already in August 2007 and has been signalling an improvement of the situation already in the autumn of 2012. An out-of-sample forecast of the STCC-GARCH model is also provided, which is both a novelty and a further robustness check for the stability of the model.
Keywords: G12; G15; F36; 330; correlation breakdowns; government bonds; monetary policy; multivariate GARCH; regime changes